SODIUM-GLUCOSE LINKED COTRANSPORTER 2 INHIBITOR: A NEW HORIZON IN THE TREATMENT OF TYPE-2 DIABETES - BISHT, REKHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Hyperglycemia is a key therapeutic focus in the management of patients with type 2 diabetes (T2D) mellitus. The various therapeutic classes of antidiabetic drugs presently existing in the market are not sufficiently effective in maintaining long-term glycemic control in most of the diabetic patients, even when used in combination. The undesirable adverse effects of these drugs, such as hypoglycemia, weight gain, and hepatic and renal toxicity, have escalated the demand for the discovery of new and safer antidiabetic drugs. The progressive nature of T2D requires practitioners to periodically evaluate patients and intensify glucose-lowering treatment once glycemic targets are not attained. Sodium-glucose cotransporter 2 inhibitors (SGLT2-is) are the new class of antidiabetic medications that are approved (2013) by the Food and Drug Administration recently for treating diabetes. These inhibitors block the SGLT2 protein involved in glucose reabsorption from the proximal renal tubule resulting in escalated glucose excretion and lower blood glucose levels. These inhibitors exhibit favorable effects beyond glucose control, such as consistent body weight, blood pressure, and serum uric acid reductions. This review highlighted the brief updates of SGLT2-i, their benefits, and adverse effects.